The Influence of Leadership Style and Mandor Discipline on the Work Performance of Harvest Employees at PT. PP London Sumatra Indonesia Tbk, Tanjung Makmur Estate, Gunung Bayan Village, West Kutai Regency, East Kalimantan Province - Andi Lelanovita Sardianti; Mellisa Pebrianti; Puspita; Ernita Obeth; Muhamad Yazid Bustomi (Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the influence of leadership style and foreman discipline on the work performance of harvest employees at PT. PP London Sumatra Indonesia Tbk, Tanjung Makmur Plantation. The leadership and foreman work discipline factors play an important role in increasing employee harvest productivity, which ultimately affects the company's harvest results. In conducting this study, a quantitative approach was used with statistical testing and data collection techniques through questionnaires distributed to 35 harvest employees and 3 foremen and supported by company data which were then processed in statistical tests using software (SPSS 26), namely multiple linear regression tests, t-tests, F-tests, and calculating the determination coefficient (Adjusted R2). The results showed that the leadership style and foreman discipline had a simultaneous effect on the work performance of harvest employees. However, partially both showed a negative effect caused by the implementation style that was not yet appropriate, less communicative, and inconsistent. This has an impact on decreasing employee enthusiasm and work results. Therefore, this study recommends that the company re-implement the leadership style and foreman discipline system to be more adaptive, communicative, and build a productive work environment.